Electrophoretic deposition of carbon nanotubes onto zinc substrates for electrode applications - Napapon Massa-Angkul,; Jesper T.N. Knijnenburg,; Pornnapa Kasemsiri,; Chaiyaput Kruehong,; Günther G. Scherer,; Prinya Chindaprasirt,; Kaewta Jetsrisuparb, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Carbon nanotubes (CNTs) as nanostructured materials have been widely used to improve electrochemical performance of electrode materials for various batteries and electrolyzers. The purpose of this work was to investigate the electrophoretic deposition (EPD) of multi-walled CNTs (MWCNTs) onto Zn plates for application in aqueous Zn ion batteries. The effects of MWCNTs on Zn oxidation and reduction were assessed using cyclic voltammetry. Before EPD, the MWCNTs were modified using H2 SO4 /HNO3 under reflux to improve dispersion stability in water. Acid modification shortened the MWCNTs but did not cause significant changes in crystallinity, tube diameter, and interlayer spacing. In a second step, the acid modified MWCNTs were homogeneously deposited onto a conductive Zn plate by EPD. Cyclic voltammetry data indicate that the coating of Zn with MWCNTs does not affect the Zn oxidation and reduction potential. Oxidation of Zn eventually leads to formation of a ZnO film, protecting the Zn surface from corrosion. When the protective ZnO film is dissolved, the underlying Zn is oxidized, leading to unfavorable loss of Zn. The presence of MWCNTs reduces oxidation during the cathodic sweep, implying that the MWCNT coating partially protects the underlying Zn surface from oxidation during charging. In addition, the MWCNT coated electrodes also facilitate hydrogen formation and show less oxygen limitation reaction, and could thus be envisaged as possible electrode materials for energy storage devices such as bifunctional electrodes for electrolyzers or air cathodes for batteries or fuel cells.